Opioid-prescribing Practices in Chronic Cancer Pain in a Tertiary Care Pain Clinic - Thota, Raghu S (Medknow Publications & Media Pvt Ltd, 2011)
INTRODUCTION: Under treatment of pain is a recognized global issue. Opioid analgesic medication is the mainstay of treatment in cancer patients as per the World Health Organization (WHO) pain relief ladder, yet 50% of cancer patients worldwide do not receive adequate pain relief or are undertreated. AIM: The aim of this study was to audit the ongoing opioid-prescribing practices in our tertiary cancer pain clinic during January–June 2010. MATERIALS & METHODS: The prescribed type of opioid, dose, dosing interval, and laxatives details were analyzed. RESULTS: Five hundred pain files were reviewed and 435 were found complete for audit. Three hundred forty-eight (80%) patients were prescribed opioids. Two hundred fifty-nine (74.4%) received weak opioids while 118 (33.9%) received strong opioids. A total of 195 (45%) patients had moderate and 184 (42%) had severe pain. Ninety-three (26.7%) patients received morphine; however, only 31.5% (58 of 184) in severe pain received morphine as per the WHO pain ladder. Only 73 of 93 (78.4%) patients received an adequate dose of morphine with an adequate dosing interval and only 27 (29%) were prescribed laxatives with morphine. CONCLUSION: This study shows that the under treatment of pain and under dosing of opioids coupled with improper side effect management are major issues.